An algorithm based mesh check-sum fault tolerant scheme for stream ciphers. (29th June 2009) - Zhang, C.N.; Liu, Xiao Wei
To enhance the security and reliability of the widely-used stream ciphers, a novel mesh check-sum ABFT scheme for stream ciphers is developed. By utilising the ready-made arithmetic unit in stream ciphers, single and multiple errors can be detected and corrected in a cheap way. To meet different requirements in practical applications, 4D mesh check-sum ABFT scheme is proposed which can be applied to RC4 or other stream ciphers. The 2D mesh check-sum ABFT scheme is able to detect and correct single error with high efficiency. The 4D mesh check-sum ABFT scheme is capable of correcting up to three errors located randomly in an N-element matrix with acceptable computation and bandwidth overhead. The workload can be remarkably reduced when most communications are error-free. Our scheme also provides one-to-one mapping between index and check-sum, so that error can be located and recovered by easier logic and simpler operation.